P3.017 Chlamydia Trachomatis Repeat Testing in Australia. (13th July 2013) - Lim, M; Dimech, W; Gemert, C Van; Boyle, D; McCarthy, D; Weaver, E; Donovan, B; Hellard, M
Abstract : Background: Current guidelines recommend that sexually active people aged under 25 are screened annually for Chlamydia. Those testing positive should be retested around 12 weeks later to detect re-infection. The Australian Collaboration for Chlamydia Enhanced Sentinel Surveillance (ACCESS) Laboratory Network has collected chlamydia testing data from 15 Australian public and private laboratories since 2008. This study reviews the frequency of repeat testing for C. trachomatis. Methods: Chlamydia test results and associated demographic data were extracted from participating laboratories' information systems, de-identified with a non-reversible unique code and sent to a central database using GRHANITE ® software. Using the unique identifier, cases of multiple testing episodes from individuals were reviewed to determine the frequency of repeat testing. Results: 641, 302 chlamydia test results were collected from 547, 761 individuals during the calendar years 2008–2010; 49, 655 (7.7%) were positive. Overall, 9.6% individuals had multiple testing episodes, increasing to 23.4% among those with an initially positive result. The mean number of testing episodes per individual was 1.11 (range 1–29) and mean time between repeat tests was 201 days following negative samples but 95 days after a positive sample. Among individuals who had a repeat test, for those with a negative result 19.6% of repeat tests were performed within 42 days, 42.8% within 120 days and 86.0% within 13 months. This is compared with 41.9% (≤ 42 days), 76.6% (≤ 120 days) and 96.6% (≤ 13 months) for repeat tests following an initially positive result. Conclusion: Individuals with positive test results were found to be re-tested more frequently and earlier than those with negative test results. However, less than one quarter of individuals who tested positive for chlamydia were re-tested and over 40% of these were re-tested too soon after initial diagnosis (< 6 weeks), risking a false positive test result.